Quality of Counselling, Exposure to Vaccination Messages, and Caregivers’ Knowledge on the Uptake of Pentavalent Vaccine in Six Northern Nigerian States - Matthew Alabi; Leanne Dougherty; Eno-Obong Etim; Adebola Adedimeji (Advances in Public Health)
Background. Pentavalent (Penta) vaccine coverage for children aged 12–23 months is used as the prime substitute for determining vaccination coverage and monitoring the performance of the national immunization program. However, the coverage for Penta vaccine in Nigeria remains low. Quality interaction between caregivers and providers and access to appropriate information are associated with healthcare utilization and acceptance of recommended health behaviours. This study examines the quality of counselling (QOC), caregivers’ exposure to vaccination messages, and child’s uptake of the Penta vaccine. Methods. This was a cross-sectional study that utilized quantitative data obtained through a survey. Caregivers (n = 561) of children aged 2–24 months accessing child vaccination services who received Penta vaccines at randomly selected health facilities (n = 163) offering routine immunization (RI) services were surveyed. Penta uptake was coded as binary; hence, binary logistic regression was performed using Stata 14. Result. We found that 56% of the caregivers received quality counselling. Although awareness of child vaccination was high (70%), two-thirds had limited exposure through health communication channels. The uptake of all three doses of Penta vaccine was 43% among eligble children. Factors associated with Penta uptake include caregivers’ knowledge of when a child should receive their first vaccination (aOR = 2.08 and 95% CI = 1.01–4.29), sources of child vaccination messages, namely, place of worship (aOR = 2.78 and 95% CI = 1.15–6.67), community health workers (CHWs; aOR = 1.95 and 95% CI = 1.14–3.34), community leader (aOR = 2.21 and 95% CI = 1.11–4.41), and residence in the northwest region (aOR = 2.60 and 95% CI = 1.51–4.48). Conclusion. Given the low quality of counselling and the positive influence of religious and traditional leaders, interventions that prioritize strengthening patient–provider interaction and community structure are crucial for increasing child vaccination coverage in Nigeria.